A suitable strategy to find IAA metabolism mutants - Casanova-Sáez, Rubén; Pěnčík, Aleš; Muñoz-Viana, Rafael; Brunoni, Federica; Pinto, Rui; Novák, Ondřej; Ljung, Karin; Mateo-Bonmatí, Eduardo (Physiologia plantarum, 2025)
Indole-3-acetic acid (IAA), the most common form of auxin, is involved in a great range of plant physiological processes. IAA is synthesized from the amino acid tryptophan and can be transported and inactivated in a myriad of ways. Despite intense research efforts, there are still dark corners in our comprehension of IAA metabolism and its interplays with other pathways. Genetic screens are a powerful tool for unbiasedly looking for new players in a given biological process. However, pleiotropism of auxin-related phenotypes and indirect effects make it necessary to incorporate additional screening steps to specifically find mutants affected in IAA homeostasis. We previously developed and validated a high-throughput methodology to simultaneously quantify IAA, key precursors, and inactive forms from as little as 10 mg of fresh tissue. We have carried out a genetic screening to identify mutants involved in IAA metabolism. Auxin reporters DR5pro:VENUS and 35Spro:DII-VENUS were EMS-mutagenized and subjected to a parallel morphological and reporter-signal pre-screen. We then obtained the auxin metabolite profile of 325 M3 selected lines and used multivariate data analysis to identify potential IAA-metabolism mutants. To test the screening design, we identified the causal mutations in three of the candidate lines by mapping-by-sequencing: dii365.3, dii571.1 and dr693. These carry new alleles of CYP83A1, MIAO, and SUPERROOT2, respectively, all of which have been previously involved in auxin homeostasis. Our results support the suitability of this approach to find new genes involved in IAA metabolism.
Keywords: regulátory růstu rostlin; Arabidopsis; Mutation; fenotyp; mutace; Indoleacetic Acids; kyseliny indoloctové; Arabidopsis Proteins; Gene Expression Regulation, Plant; proteiny huseníčku; Plant Growth Regulators; regulace genové exprese u rostlin; Phenotype